Amoeboid Pyroxene Aggregates in CO3 Yamato 81020: Implications for Nebular Condensation - Fagan, Timothy J.; Komatsu, Mutsumi (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites / Hayabusa, Wed. 5 Dec. / Conference hall of the Research/Administration Building (2nd floor) at the JAXA Sagamihara Campus conference object